Advances in MALDI and Laser-Induced Soft Ionization Mass Spectrometry - Cramer, Rainer (Springer International Publishing : Imprint: Springer, 2016)
This book covers the state-of-the-art of modern MALDI (matrix-assisted laser desorption/ionization) and its applications. New applications and improvements in the MALDI field such as biotyping, clinical diagnosis, forensic imaging, and ESI-like ion production are covered in detail. Additional topics include MS imaging, biotyping/speciation; large-scale, high-speed MS sample profiling; new methods based on  MALDI or MALDI-like sample preparations; and the advantages of MALDI MS analysis over ESI (electrospray ionization).  This is an ideal book for graduate students and researchers in the field of bioanalytical sciences. This book also: • Showcases new techniques and applications in MALDI MS • Demonstrates how MALDI is preferable to ESI • Illustrates the pros and cons associated with biomarker discovery studies in clinical proteomics and various application areas, such as cancer proteomics.